A comparison between two fertilizer recommendations according to some productivity and quality indicators for tomatoes in protected agriculture (Damascus University Journal of agriculture sciences, 2026)
The research was carried out at Alsanobar Research Station – Lattakia – General Commission for Scientific Agricultural Research (GCSAR). During the two seasons 2020–2021 to determine the effect of two different fertilizer recommendations of the tomato crop (Lycopersicom esculentum) on some of the studied indicators under protected agriculture conditions.Two fertilizer treatments (T1 treatment according to a productivity of 6 tons, T2 treatment according to the Ministry’s Agricultural recommendation) in Three replications by using full random sectors. The amounts of fertilizer to be added to the crop were calculated, and the effect of the two treatments on (plant height, productivity, weight of ten fruits, and concentration of elements N, P, K in the fruits) was studied.The results showed that the proposed fertilization treatment T1 was significantly superior in terms of the length of the shoots, the weight of ten fruits, the average productivity of the greenhouse 5.8 ton/house, and the percentage of potassium, nitrogen and phosphorus in the fruits compared to the T2 fertilization treatment recommended by the Ministry's Agricultural recommendation.
Keywords: Tomatoes; Productivity; Protected Agriculture; Fertilizer Recommendation; N, P, and K Elements